Solar Energy 2005
DOI: 10.1115/isec2005-76035
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of Phase Change Material Peak Load Shifting

Abstract: Peak demand for electricity in many parts of the country, and particularly the desert southwest, is of critical concern to utilities. Any reasonable solutions that can be used for shifting some of the peak demand to off-peak should be seriously considered. For locations with high air conditioning demand, one possibility is to use a phase-change material in the ceiling insulation that may melt during peak demand periods and then be refrozen off peak. The purpose of our work is the development of a numerical mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 0 publications
0
11
0
1
Order By: Relevance
“…The goal in implementing composite PCM walls is to significantly reduce and time-shift the maximum thermal load on the building in order to reduce and smooth out the electricity demand for heating and cooling. This could also help ratepayers take advantage of TOU electricity rate schedules while reducing the ecological footprint of buildings [3,4,[9][10][11][12]. The choice of PCM should be adapted to the climate and building orientation so as to maximize the above mentioned benefits.…”
Section: Introductionmentioning
confidence: 96%
“…The goal in implementing composite PCM walls is to significantly reduce and time-shift the maximum thermal load on the building in order to reduce and smooth out the electricity demand for heating and cooling. This could also help ratepayers take advantage of TOU electricity rate schedules while reducing the ecological footprint of buildings [3,4,[9][10][11][12]. The choice of PCM should be adapted to the climate and building orientation so as to maximize the above mentioned benefits.…”
Section: Introductionmentioning
confidence: 96%
“…The modeling and optimal control of the building integrated PCM are essential for accurately estimating the thermal performance. An idealized model for peak load shifting and a simplified RC-model have been respectively developed for investigating the indoor thermal performance (Halford and Boehm 2007;Zhu et al 2010). The results showed that the developed models could represent the thermal characteristics of the PCM quite well.…”
Section: Phase Change Materialsmentioning
confidence: 98%
“…From the different numerical models available in the literature, we considered that used by Halford et al [15], which is based on an explicit time-variant scheme, in which the thermal balance equation at the bi-phase interface is formulated in a manner that is more adherent to the physical phenomenon. In particular, the discontinuity of the heat flux at the interface is considered substituting the relative incremental ratio DX M =Dt at the derivative dX M =dt.…”
Section: Comparison Between Analytical and Numerical Solutionmentioning
confidence: 99%
“…While Halford [15] examined the influence of the layer thickness and of the outdoor climatic conditions on the time lag and on the attenuation of the peak load. Instead, the influence of the position and the melting temperature of the PCM layer on the annual energy requirement has been studied by Mathieu-Potvin et al [16].…”
Section: Introductionmentioning
confidence: 99%